Subject-Controlled, On-demand, Dorsal Genital Nerve Stimulation to Treat Urgency Urinary Incontinence; a Pilot - van Breda, Hendrikje M. K.; Farag, Fawzy F.; Martens, Frank M. J.; Heesakkers, John P. F. A.; Rijkhoff, Nico J. M. (Frontiers in Neuroscience, 2016)
Objectives: To evaluate the effect of subject-controlled, on-demand, dorsal genital nerve (DGN) stimulation on non-neurogenic urgency urinary incontinence (UUI) in a domestic setting. Materials and Methods:Non-neurogenic patients >18 years with overactive bladder symptoms and UUI were included. Exclusion criteria were mainly stress urinary incontinence. Patients underwent 1 week of subject-controlled, on-demand, DGN stimulation, delivered by a percutaneously placed electrode near the DGN connected to an external stimulator (pulse-rate 20 Hz, pulse-width 300 μs). Patients activated the stimulator when feeling the urge to void and stimulated for 30 s. The amplitude was set at the highest tolerable level. A bladder diary including a severity score of the UUI episodes/void (scores: 0 = none, 1 = drops, 2 = dashes, 3 = soaks) and a padtest was kept 3 days prior to, during, and 3 days after the test period. The subjective improvement was also scored. Results: Seven patients (4 males/3 females) were enrolled, the mean age was 55 years (range 23–73). Six completed the test week. In the remaining patient the electrode migrated and was removed. 5/6 finalized the complete bladder diary, 1/6 recorded only the heavy incontinence episodes (score = 3). 4/6 completed the padtest. In all patients who finalized the bladder diary the number of UUI episodes decreased, in 3/5 with ≥60%. The heavy incontinence episodes (score = 3) were resolved in 2/6 patients, and improved ≥80% in the other 4. The severity score of the UUI episodes/void was improved with ≥ 60% in 3/5 patients. The mean subjective improvement was 73%. Conclusion: This feasibility study indicates that subject-controlled, on-demand DGN stimulation using a percutaneously placed electrode is possible over a longer time period, in a home setting, with a positive effect on non-neurogenic overactive bladder symptoms with UUI. Although the placement is an easy procedure, it is difficult to fixate the electrode to keep it in the correct position. Improvements in hardware, like a better fixated electrode and an easy to control stimulator, are necessary to make SODGNS a treatment possibility in the future.